Characteristics of Risk Factors and Clinical Manifestations of Non-Hemorrhagic Stroke In Patients At Ibnu Sina Hospital, Makassar, 2023–2024 - Muh. Althaf Firjatullah; Erlin Syahril; Suci Noviyanah Ansary; Moch. Erwin Rachman; Dwi Pratiwi (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Non-hemorrhagic stroke is the most common type of stroke and a leading cause of morbidity and disability. This condition is generally triggered by blood flow disorders due to atherosclerosis, thrombosis, or embolism, with clinical manifestations such as sudden weakness, speech disorders, and decreased consciousness. In Indonesia, including South Sulawesi, the prevalence of stroke remains high, making the identification of risk factors and clinical symptoms crucial for optimal management. This study aims to describe in detail the risk factors for non-hemorrhagic stroke in patients recorded in the medical records of Ibnu Sina YW UMI Hospital in Makassar from 2023 to 2024, as well as to describe in detail the clinical manifestations of non-hemorrhagic stroke in patients recorded in the medical records of Ibnu Sina YW UMI Hospital in Makassar from 2023 to 2024. This study was conducted using a descriptive design through a cross-sectional approach. This type of research is quantitative. The results showed that the most dominant risk factor in non-hemorrhagic stroke patients at Ibnu Sina YW UMI Hospital in Makassar in 2023–2024 was hypertension (92.3%). Other risk factors found were family history (57.7%), genetic factors (53.8%), diabetes mellitus (23.1%), history of heart disease (13.5%), and dyslipidemia (11.5%). These findings indicate that the majority of patients had more than one risk factor, with hypertension being the main factor contributing to cerebral ischemia. The most common clinical manifestations were hemiparesis (90.4%), followed by vertigo (44.2%), ataxia (36.5%), aphasia (34.6%), nausea and vomiting (19.2%), and hemianesthesia (11.5%). This pattern shows that neurological deficits in the form of motor disorders are the most prominent symptoms in non-hemorrhagic stroke patients. This study shows that hypertension is the most dominant risk factor in non-hemorrhagic stroke patients, accompanied by family history and genetic factors. The most common clinical manifestations were hemiparesis, followed by vertigo, ataxia, and aphasia. These findings emphasize the importance of early detection of risk factors and recognition of characteristic neurological symptoms for the optimization of non-hemorrhagic stroke management.